Mechanical Behaviour and Fractured Surface Analysis of Bauxite Residue and Graphite Reinforced Aluminium Hybrid Composites (Fracture and Structural Integrity, 2022)
Composite materials application areas have gradually grown, allowing them to reach and conquer new markets from consumer products to specialized niche applications, advanced composite materials make up a significant portion of the engineered materials industry. The purpose of this study is to investigate the mechanical properties of Aluminum (Al), Red Mud particle (RMp), Graphite particle (GRp) hybrid composites. The different combinations of Rm and Gr wt. % were used to prepare Al-Rm-Gr and Al-Gr-Rm hybrid composites. The mechanical properties namely Ultimate tensile strength, Compressive strength and Hardness of prepared hybrid composites are tested to know the influence of reinforcements in Al-8011 alloy. Synthesis of Aluminum-Red Mud-Graphite hybrid composites done by Stir casting method. Drastic reduction in grain size (Grain refinement) was observed in Scanning Electron Microscopic images of fractured surfaces of the tensile specimens, with addition of RMp and GRp to the matrix alloy thus soft alloy is turned into hard and brittle material. Among all the compositions of hybrid composites series AG8R10 was observed to be higher compressive strength and hardness while AR8G10 has higher ultimate tensile strength.
Keywords: Stir casting; Redmud; fracture; Al-8011 alloy